Method for Establishing New Cycloidal Tooth Profile based on Rolling-sliding Effect - Yanhua Wang; Chaoyang Li; Ye Zhang; Bingkui Chen (Jixie chuandong)
Aiming at the sliding phenomenon between the cycloidal gear and pinwheel in the actual meshing process of the cycloid pinwheel transmission，a novel cycloid tooth profile modeling method，in which using a sliding function to represent the slide between the pinwheel and the cycloidal gear in the cycloid pinwheel transmission，is proposed. Based on the differential geometry and gear meshing theory，the tooth profile equation of the rolling-sliding cycloidal gear is derived，the meshing function is determined，the calculation method of comprehensive curvature radius and contact stress of the rolling-sliding cycloidal gear are given. A new cycloid tooth profile，based on hypothetical sliding function which parameters are selected with experience，is constructed. The tooth profile，comprehensive curvature radius and contact stress of the new tooth profile and that of the standard cycloidal tooth profile are compared. A rolling-sliding cycloid gear is trial-produced and applied to the RV reducer，the accelerated fatigue test under 2.5 times load on the prototype of new RV reducer is completed. The deviation of the rolling-sliding cycloid tooth profile before and after the test is compared，and the result shows the correctness and feasibility of the new modeling method for the rolling-sliding cycloid tooth profile.